1995
DOI: 10.1111/j.1600-0536.1995.tb00839.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin disease and contact sensitivity in house painters using water‐based paints, glues and putties

Abstract: A dermatologic investigation of 202 construction painters included patch testing with the TRUE Test standard series and ingredients of water-based paints, glues and putties (painters' series). 32 painters had current eczema and 16 had a history of previous eczema. Of these, 16 and 9, respectively, had current and previous histories of hand eczema. Irritant reactions on the hands, characterized by dry, erythematous finely fissured skin, which healed within a few days of skin rest, were found in 18 painters. 8 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 44 publications
4
37
0
3
Order By: Relevance
“…4.1% of English patients with occupational der-matitis were positive to colophony -the majority employed in the furniture industry (13); 1.3% of Swedish house-painters were colophony positive (14); and 13.9% of German venous leg ulcer patients with contact dermatitis were colophony positive (15). A Dutch study showed an increase in the positivity rate of colophony within a patch test clinic from 1.2% to 1.8% between 1974 and 1984 (16), and a similar Greek study plotted a significant rise in prevalence between 1984 and 1995 (17).…”
Section: Prevalence Of Colophony Allergymentioning
confidence: 99%
See 1 more Smart Citation
“…4.1% of English patients with occupational der-matitis were positive to colophony -the majority employed in the furniture industry (13); 1.3% of Swedish house-painters were colophony positive (14); and 13.9% of German venous leg ulcer patients with contact dermatitis were colophony positive (15). A Dutch study showed an increase in the positivity rate of colophony within a patch test clinic from 1.2% to 1.8% between 1974 and 1984 (16), and a similar Greek study plotted a significant rise in prevalence between 1984 and 1995 (17).…”
Section: Prevalence Of Colophony Allergymentioning
confidence: 99%
“…Colophony allergy has been reported to solder flux in the electronic industry (19), to pine wood and saw dust in the furniture-making industry (13,20), to paints in house-painters (14), to paper in paper manufacturing (21) and to cutting oil and soap water in machine operators (22). Air-borne contact dermatitis from colophony has been described in the manufacturing of linoleum floor coverings and milk cartons (23).…”
Section: Sources Of Colophony Exposurementioning
confidence: 99%
“…The product labels and material safety data sheets supplied with these products stipulate that the material is corrosive and a contact allergen, and not meant to come into contact with the skin (36). In prospective surveys of specific industries and certain workplaces, isothiazolinones are well-recognized allergens (27)(28)(29). 150 metal workers in a factory using MCUMI in a coolant oil were offered patch testing, and of the 27 who were tested to 50 ppm, 44% had a positive patch test to MCIIMI, which means, at a bare minimum, that 7% of the factory personnel were sensitized (27).…”
Section: Occupationalmentioning
confidence: 99%
“…299 members of a painters organization were sent a questionnaire and 202 of these were patch tested. 3 painters were deemed to have a probably relevant contact allergy to MCI/MI, as well as 2 with a doubtful reaction (28). In a factory making acrylate-based paint and glue binders, 9/51 (17.6%) of the current production workers who were patch tested were allergic to MCI/MI, with 4 of these workers having current dermatitis (3 hands and 1 leg).…”
Section: Occupationalmentioning
confidence: 99%
“…Además es muy relevante la presencia de este preservativo en productos de limpieza de uso doméstico y a concentraciones más elevadas en productos de utilización industrial, como los aceites de corte, emulsiones de látex, pinturas al temple, reveladores de fotografía y radiografía, aceites para motores diesel, pesticidas, abrillantadores, tintas de imprenta... [5][6][7][8][9] .…”
Section: Introductionunclassified